1984
DOI: 10.3102/00028312021003597
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Peer Acceptance, Social Impact, and Academic Achievement in Middle Childhood

Abstract: The purpose of this study was to investigate the relationship of academic achievement to four categories of social status including popular, rejected, isolated, and amiable, and to the variables of peer acceptance and social impact. Subjects were 145 elementary school children, grades 3 through 6. The children responded to a questionnaire designed to assess peer acceptance as well as rejection. Data consisted of (a) acceptance scores based on the predominance of either acceptance or rejection responses from pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Social competence in childhood is a powerful predictor of academic achievement (Berghout Austin & Draper, 1984;Green, Forehand, Beck, & Vosk, 1980;Wentzel, 1992). Children who are accepted by their peers or demonstrate prosocial behaviors in school tend to be high achievers, whereas socially rejected children appear to be at high risk for academic failure.…”
Section: A Focus On Social Emotional Developmentmentioning
confidence: 99%
“…Social competence in childhood is a powerful predictor of academic achievement (Berghout Austin & Draper, 1984;Green, Forehand, Beck, & Vosk, 1980;Wentzel, 1992). Children who are accepted by their peers or demonstrate prosocial behaviors in school tend to be high achievers, whereas socially rejected children appear to be at high risk for academic failure.…”
Section: A Focus On Social Emotional Developmentmentioning
confidence: 99%
“…Interestingly, variance in end of first-year GPA was explained by ADHD symptoms and social acceptance but not by reciprocated friendships. Although studies have consistently linked greater peer acceptance with better academic performance (e.g., Austin & Draper, 1984;Wentzel & Caldwell, 1997), findings on the association between friendships and academic achievement have been admittedly mixed (Swenson Goguen, Hiester, & Nordstrom, 2010;Wentzel, Barry, & Caldwell, 2004). It has been suggested that acceptance by a larger peer group motivates interest in classroom activities (Wentzel, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Od prosječnih se učenika razlikuju po tome što ih vršnjaci češće smatraju odličnim učenicima te po tome što učitelji smatraju da više pomažu drugim suučenicima (Wentzel i Asher, 1995). Popularni učenici imaju bolji školski uspjeh te se češće upuštaju u pozitivnije interakcije s vršnjacima od onih prosječnih (Berghout Austin i Draper, 1984). Školski uspjeh učenika u dosadašnjim istraživanjima operacionaliziran je na različite načine pa se pojam školskog uspjeha često izjednačuje s pojmovima školskog učinka, školske kompetencije, školske sposobnosti i sl.…”
Section: Uvodunclassified